Considering the Legal Efforts of Dispute Decisions on Election Results of the Constitutional Court (Law Research Review Quarterly, 2018)
Article 24C Paragraph (1) of the 1945 Constitution confirms that the Constitutional Court (MK) has the authority to adjudicate at the first and last level with a final decision to review the Law against the Constitution. Related to election disputes, the Constitutional Court has the authority to adjudicate dispute cases and the Constitutional Court's decision is final and binding. It is undeniable that this matter becomes a debate, what if in the course of finding new evidence (novum) or what is the possibility of legal remedies in election disputes. This paper will try to explore what is the philosophy of the legal remedies and how it might be used in election disputes. By appealing to philosophical thinking it is hoped that a new thought can be drawn on these possibilities.